A Rare Case Of Streptococcus Mitis Infective Endocarditis Complicated By Heart Failure In A Lactating Mother With Recurrent Breast Engorgement - Hakimah S; Liyana Najwa IM; Hoo FK; Siti Zulaikha Z; Haikal Hafiz WZWZ; Tan WM (Academy of Family Physicians of Malaysia, 2024)
Malaysian Family Physician 2019; Volume 14, Number 2